Polish consumer categorisation of grilled beef at 6 mm and 25 mm thickness into quality grades, based on Meat Standards Australia methodology. (March 2020) - Pogorzelski, Grzegorz; Woźniak, Katarzyna; Polkinghorne, Rod; Półtorak, Andrzej; Wierzbicka, Agnieszka
Abstract: Meat Standards Australia (MSA) methodology was used to evaluate the sensory categorization of beef by Polish consumers. A significant quality range was created by utilisation of 3 muscles, M. psoas major, M. longissimus thoracis et lumborum, and M. semimembranosus from 22 divergent bull carcasses (Holstein-Friesian crosses with Limousine, Hereford). Consumers evaluated every sample for selected sensory traits and chose a grade. A trend was observed for 6 mm preparation to reduce the proportion of unsatisfactory SM, with a consequent increase in 3star counts, in contrast to reducing the proportion of PM 5star and LTL 4star with an increase in the lower categories. Within each thickness Polish consumers clearly distinguished between grades, defined by MQ4 (Meat Quality, 4 variables) boundaries derived from discriminant analysis. Similar accuracy was achieved for both thicknesses. It was concluded that the MQ4 score could be successfully used to support a meat quality grading system in Poland.